Male Breast Cancer: An Updated Review of Patient Characteristics, Genetics, and Outcome - Vidhu Shekhar Khare; Farhanul Huda; Subhasis Misra; Kanmatha Reddy Amulya; Nirmal Raj; Summi Karn; Somprakas Basu (International Journal of Breast Cancer)
Male breast cancer (MBC) is a rare entity, underrepresented in population studies and clinical trials, resulting in management of MBC to be informed by current research on female breast cancer (FBC). A literature review was conducted by accessing relevant articles on 2 databases, by searching keywords “male breast cancer”. A total of 29 articles from year 2011 to 2022 were selected for this review. The authors found that male breast cancer generally occurs later in life with higher stage, higher grade, and more estrogen receptor (ER) positive tumours. Most of the studies noted the mean age for MBCs at the time of presentation as >60 years. Risk factors for male breast cancer include family history, obesity, lower physical activity, and syndromes like the Klinefelter syndrome. Positive family history is much higher in MBC compared to FBC (30.9 vs. 18.4%). BRCA 2 cancers constitute a higher proportion compared to FBCs. A lot of genetic mutations have been observed. Some show promise to assess disease-specific survival and proliferative rate like TWIST1 and RUNX3, among others. MBCs usually present with a palpable lump in central region, with a bigger size and chance of nodal involvement and metastasis compared to FBCs. They are mostly infiltrating ductal type and hormone receptor positive, with worse histological grade. Treatment usually follows the same principles as FBCs (systemic therapy, surgical excision, and radiotherapy), with poorer prognosis to same treatment approach, possibly owing to its advanced stage at presentation. This is a rare entity which requires further research to ascertain need for different management approach than FBCs.